A Primer on the Epistemology of New Commons - Issa Mansoori (ZBW - Leibniz Information Centre for Economics, 2025)
By framing development as an emergent property of collective consciousness, this paper provides a fresh epistemological lens to address local and global common challenges, such as inequality, social, cultural, and ecological degradation, and resource management through commoning. The paper argues for the `new commons', reimagining the concept of development by integrating insights from the philosophy and neuroscience of consciousness. Moving beyond economic conventional and institutionalist paradigms, it explores how development, like consciousness, functions as an interconnected and emergent system that transcends the sum of its parts. Countering neoliberal ideologies and prioritizing collective intention instead of pluralistic action, `new commons' can be defined from a different perspective. Also, distinct from Ostrom's common resource management model, the new commons framework emphasizes the societal construction of shared spaces and values through collective consciousness.
Keywords: 330; New commons; Development; Epistemology; Economic goods